2009
DOI: 10.1158/1078-0432.ccr-08-2924
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ovarian Cancer Growth by a Tumor-Targeting Peptide That Binds Eukaryotic Translation Initiation Factor 4E

Abstract: Purpose: A critical step of protein synthesis involves the liberation of the mRNA capbinding translation initiation factor eIF4E from 4EBP inhibitory binding proteins, and its engagement to the scaffolding protein eIF4G. eIF4E is a candidate target for cancer therapy because it is overexpressed or activated in many types of tumors and has tumorigenic properties. Our aim was to design and evaluate 4EBP-based peptides for their antitumor activity in ovarian cancer. Experimental Design: The ability of peptides to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 41 publications
(78 reference statements)
2
43
0
Order By: Relevance
“…Several of these show micromolar potency and have proven to be useful tool compounds for probing the role of deregulated translation in the tumorigenic process ex vivo whereas others are more potent and show in vivo efficacy in pre-clinical cancer models. As an example, proof-of-concept for targeting eIF4E/eIF4G interaction in vivo as an anti-cancer approach has been demonstrated using a 4E-BP1-derived peptide fused to an agonist of the gonadotropin-releasing hormone (GnRH), whose corresponding receptor is expressed in 80% of epithelial ovarian cancers [43]. Remarkably, the fusion peptide was able to abrogate eIF4E/eIF4G association, inhibit translation in a tumor cell-specific manner, and reduce tumor burden in a xenograft mouse model of epithelial ovarian cancer [43].…”
Section: Targeting Dysregulated Translational Control In Cancer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these show micromolar potency and have proven to be useful tool compounds for probing the role of deregulated translation in the tumorigenic process ex vivo whereas others are more potent and show in vivo efficacy in pre-clinical cancer models. As an example, proof-of-concept for targeting eIF4E/eIF4G interaction in vivo as an anti-cancer approach has been demonstrated using a 4E-BP1-derived peptide fused to an agonist of the gonadotropin-releasing hormone (GnRH), whose corresponding receptor is expressed in 80% of epithelial ovarian cancers [43]. Remarkably, the fusion peptide was able to abrogate eIF4E/eIF4G association, inhibit translation in a tumor cell-specific manner, and reduce tumor burden in a xenograft mouse model of epithelial ovarian cancer [43].…”
Section: Targeting Dysregulated Translational Control In Cancer Modelsmentioning
confidence: 99%
“…As an example, proof-of-concept for targeting eIF4E/eIF4G interaction in vivo as an anti-cancer approach has been demonstrated using a 4E-BP1-derived peptide fused to an agonist of the gonadotropin-releasing hormone (GnRH), whose corresponding receptor is expressed in 80% of epithelial ovarian cancers [43]. Remarkably, the fusion peptide was able to abrogate eIF4E/eIF4G association, inhibit translation in a tumor cell-specific manner, and reduce tumor burden in a xenograft mouse model of epithelial ovarian cancer [43]. In addition, small molecule inhibitors of eIF4E/eIF4G interaction are capable of re-sensitizing chemoresistant lymphomas to doxorubicin in the murine EĪ¼-Myc lymphoma model [44].…”
Section: Targeting Dysregulated Translational Control In Cancer Modelsmentioning
confidence: 99%
“…Dysregulation of these processes is associated with human pathologies including infertility, birth defects and cancers (Graff et al, 2008;Song and Lu, 2011). Clinical studies have shown that the eukaryotic translation initiation factor eIF4E is overexpressed in multiple cancers including ovarian, esophageal, breast, thyroid and prostate (Furic et al, 2010;Ko et al, 2009;Kouvaraki et al, 2011;Salehi and Mashayekhi, 2006). Its overexpression upregulates the translation of mRNAs for cell cycle, growth and reactive oxygen species (ROS) regulatory proteins (De Benedetti and Graff, 2004;De Benedetti and Rhoads, 1990;Rosenwald, 2004;Rosenwald et al, 1993), leading to the cancer phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…inhibition of cap-dependent protein translation via mTORC1/4EBP-1 inhibition. Recently, eIF4F inactivation is emerging as a promising approach for anti-cancer intervention [29][30][31], which could be particularly important in those cancer cells where the canonical modes of cell death are expected to be defective. The current results also emphasized the versatility of Rottlerin as anticancer drug in a variety of cellular models, which greatly differ from each other in terms of genetic/biochemical profile and chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%